Myanmar: Impacts of the Ukraine and Global Crisis on Food Systems and Poverty - Diao, Xinshen; Dorosh, Paul; Mahrt, Kristi; Minten, Bart; Pauw, Karl; Randriamamonjy, Josee; Thurlow, James (2022)
Presentation prepared by Xinshen Diao, Paul Dorosh, Kristi Mahrt, Bart Minten, Karl Pauw, Josee Randriamamonjy, and James Thurlow, all with the International Food Policy Research Institute, Washington DC. This is part of the Global Crisis Country Series.